Kaolinitic calcined clays: Factors affecting its performance as pozzolans - Tironi, Alejandra (2012)
Five natural kaolinitic clays from different regions of Argentine, with different kaolinite content, different impurities and different degree of crystallinity were calcined in a fixed-bed electrical furnace at 700 °C. Clays were characterized by X-ray diffraction (XRD) and Fourier transformed infra-red spectrometry (FTIR) that provides an index about the order/disorder of the structure. After heat treatment, the structural changes were characterized by XRD and FTIR, and pore size distribution and specific surface were determined. Their pozzolanic activity was evaluated with the Frattini test, electrical conductivity in saturated Ca(OH) 2 solution and compressive strength on mortars at 7, 28 and 90 days. Among tested clays, four of them can be classified as pozzolan by the Frattini test. The pozzolanic activity of the natural clays showed good correlation with the content of kaolinite, the inversed of structure order determined by FTIR, and the specific surface of calcined clays. This study confirms that natural clays other than pure kaolinite can be interesting pozzolanic materials when thermally activated.